Reproductive Health Indicators and Factors Affecting Menstrual Cycle Pattern among Sudanese Women with Thyroid Dysfunction - Yassin, Khalid; Sharif, Maisa; Abulea, Abd E.; Kamil, Amel; Ali, Abdel Aziem A. (Current Women's Health Reviews, 2015)
This was a cross sectional hospital based study conducted at Khartoum Teaching Hospital, Sudan, during the period of June-through December 2013 to investigate the reproductive health indicators and the factors affecting menstrual cycle pattern among women with thyroid dysfunction. A total of 210 women had been enrolled, 128 (61.0%) were married, and 72(39%) were single. Of the total respondents 51.9%, 46.2% and 1.9% (4) had hypothyroidism, hyperthyroidism and thyroiditis respectively. Among the total respondents 53.9% have normal menstrual cycle pattern, 19% suffered from polymenorrhea, 12.4% reported oligomenorrhea, 9% have amenorrhea, 4.3% have vaginal spotting, and 1.4% suffered from menorrhagia. Also among 128 married patients the bad obstetric outcome was reported as follow: miscarriage (47.6%), stillbirth delivery (7.8%), preterm birth (5.4%) and neonate with congenital cerebral palsy (0.7%). Interestingly 18 women suffered from premature ovarian failure and 20 women had primary infertility. Menstrual cycle abnormalities among women with thyroid dysfunction were significantly associated with long duration of the disease ≥5 years (OR=0.4; CI=, 0.2-0.8; P =0.016), co-morbidity (OR=9.0; CI=, 3.1-28.8; P =0.000), and poor compliance to treatment (OR=0.2; CI=, 0.09-0.8; P =0.021). Thus polymenorrhea is the most predominant menstrual cycle problem observed among Sudanese women with thyroid dysfunction. Menstrual cycle abnormalities among women with thyroid dysfunction were significantly associated with long duration of the disease ≥5 years, co-morbidity and poor compliance to treatment.
Keywords: reproductive